Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 5 - Section 5.3 - The Fundamental Theorem of Calculus - 5.3 Exercises: 21

Answer

$\displaystyle\int\limits_0^2(\dfrac{4}{5}t^{3}-\dfrac{3}{4}t^{2}+\dfrac{2}{5}t)dt=2$

Work Step by Step

$\displaystyle\int\limits_0^2(\dfrac{4}{5}t^{3}-\dfrac{3}{4}t^{2}+\dfrac{2}{5}t)dt$ Integrate each term separately: $\displaystyle\int\limits_0^2\dfrac{4}{5}t^{3}dt-\displaystyle\int\limits_0^2\dfrac{3}{4}t^{2}dt+\displaystyle\int\limits_0^2\dfrac{2}{5}tdt=...$ Take the constants out of the integral and continue integrating: $...=\displaystyle\dfrac{4}{5}\int\limits_0^2t^{3}dt-\displaystyle\dfrac{3}{4}\int\limits_0^2t^{2}dt+\displaystyle\dfrac{2}{5}\int\limits_0^2tdt=...$ $...=\dfrac{4}{5}(\dfrac{1}{4})t^{4}-\dfrac{3}{4}(\dfrac{1}{3})t^{3}+\dfrac{2}{5}(\dfrac{1}{2})t^{2}\Big|_0^2=...$ $...=\dfrac{1}{5}t^{4}-\dfrac{1}{4}t^{3}+\dfrac{1}{5}t^{2}\Big|_0^2=...$ Use the second part of the fundamental theorem of calculus to get the result: $...=\Big[\dfrac{1}{5}(2)^4-\dfrac{1}{4}(2)^{3}+\dfrac{1}{5}(2)^2\Big]-\Big[\dfrac{1}{5}(0)^4-\dfrac{1}{4}(0)^{3}+\dfrac{1}{5}(0)^2\Big]=...$ $...=\dfrac{1}{5}(16)-\dfrac{1}{4}(8)+\dfrac{1}{5}(4)=\dfrac{16}{5}-2+\dfrac{4}{5}=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.